2020
DOI: 10.3390/ani10091659
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Fungal-Pretreated Corn Straw Improves Health and Meat Quality of Lambs Infected with Gastrointestinal Nematodes

Abstract: Infections with gastrointestinal nematodes (GIN) adversely affect meat color in lambs. Although white-rot fungi (WRF) pretreatment increases nutritional value and fiber digestion of corn straw for lambs, whether it can improve meat quality of lambs infected with GINs is unknown. The objective of this experiment was to study effects of feeding WRF-pretreated corn straw on the health and meat quality of lambs infected with GINs. Sixteen healthy Ujumqin lambs were orally drenched with 3rd-stage GINs larvae and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Aged for (7) days, similar observations were reported in lambs fed herbal plants (24). Based, (74) showed that increased redness value (P≤0.01) and reduced yellow appearance and lightness values (p ≤0.05) of both semimembranosus (SM) and longissimus thoracis et lumborum (LTL) muscles of lambs infected with gastrointestinal nematodes fed whiterot fungi-pretreated corn straw. Dietary coriander seeds made a significant different for lightness and yellow appearance parameters.…”
Section: Colorsupporting
confidence: 65%
See 1 more Smart Citation
“…Aged for (7) days, similar observations were reported in lambs fed herbal plants (24). Based, (74) showed that increased redness value (P≤0.01) and reduced yellow appearance and lightness values (p ≤0.05) of both semimembranosus (SM) and longissimus thoracis et lumborum (LTL) muscles of lambs infected with gastrointestinal nematodes fed whiterot fungi-pretreated corn straw. Dietary coriander seeds made a significant different for lightness and yellow appearance parameters.…”
Section: Colorsupporting
confidence: 65%
“…Dietary quercetin did not affect loin tenderness in Hanwoo cattle (64). It was also seen that adding white-rot fungi-pretreated corn straw to the diets has been improved tenderness of lamb meat (74). (67) reported that shear force values decreased significantly (P<0.05) in meat of goats fed diet supplemented with various parts of Andrographis Paniculate (APL) or Andrographis Paniculate whole plant (APW) because…”
Section: Tendernessmentioning
confidence: 96%
“…The modification of lignin structure (delignification) will increase the access to cellulose and hemicellulose and enhance the digestibility of the lignocellulosic biomass. Many studies have evaluated the effect of biological treatment on lignocellulosic biomass with fungi, mainly in sheep [ 12 , 13 , 14 , 15 , 16 ], cattle [ 17 , 18 , 19 , 20 ], and rabbits [ 21 , 22 , 23 ]. In this context, the objective of this study was to evaluate the dietary incorporation of untreated and fungi-treated grape stalks with Lentinula edodes on the diets of growing rabbits.…”
Section: Introductionmentioning
confidence: 99%